A novel BCL11A polymorphism influences gene expression, therapeutic response and epilepsy risk: A multicenter study - Wang, Shitao; Cai, Xuemei; Liu, Shiyong; Zhou, Qixin; Wang, Ting; Du, Sunbing; Wang, Dan; Yang, Fei; Wu, Qian; Han, Yanbing (Frontiers in Molecular Neuroscience, 2022)
Background Genetic factors have been found to be associated with the efficacy and adverse reactions of antiseizure medications. BCL11A is an important regulator of the development of neuronal networks. However, the role of BCL11A in epilepsy remains unclear. This study aimed to evaluate the genetic association of BCL11A with the susceptibility to develop epileptic seizures and therapeutic response of patients with epilepsy in Han Chinese. Methods We matched 450 epilepsy cases with 550 healthy controls and 131 drug-resistant epilepsy patients with 319 drug-responsive epilepsy patients from two different centers. Genetic association analysis, genetic interaction analysis, expression quantitative trait loci analysis and protein–protein interaction analysis were conducted. Results Our results showed that rs2556375 not only increases susceptibility to develop epileptic seizures (OR = 2.700, 95% = 1.366–5.338, p = 0.004 and OR = 2.984, 95% = 1.401–6.356, p = 0.005, respectively), but also increases the risk of drug resistance(OR = 21.336, 95%CI =2.489–183.402, p = 0.005). The interaction between rs2556375 and rs12477097 results in increased risk for pharma coresistant. In addition, rs2556375 regulated BCL11A expression in human brain tissues (p = 0.0096 and p = 0.033, respectively). Furthermore, the protein encoded by BCL11A interacted with targets of approved antiepileptic drugs. Conclusion BCL11A may be a potential therapeutic target for epilepsy. Rs2556375 may increase the risks of epilepsy and drug resistance by regulating BCL11A expression in human brain tissues. Moreover, the interaction between rs2556375 and rs12477097 results in increased risk for drug resistance.